2021
DOI: 10.53293/jasn.2021.4101.1070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Aerodynamics of Synthesized Polymeric Nanofibers via Electrospinning Process to Capture PM10 and PM2.5 from Air

Abstract: Air quality is an important factor for human breathing requirements. The presence of the particulate matter which is a mixture of solid particles and liquid droplets presence in atmosphere such as PM10 and PM2.5 in the indoor air leads to fatal problems for human health. In the present investigation, two types of nanofilters (polyacrylonitrile PAN, 15wt.% and polyvinyl alcohol PVA 12wt.%) were synthesized using the electrospinning method. The polymeric solutions were prepared under high mixing conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…2, showed that the overall structure of the synthesized nanofiber is consistent with the conventional polyacrylonitrile (PAN) structure. As a result, a distinctive diffraction peak for the structure was observed at a 2θ value of 17.1 [42]. This peak is clear and strong and has a standard position at the phase (100).…”
Section: Resultsmentioning
confidence: 92%
“…2, showed that the overall structure of the synthesized nanofiber is consistent with the conventional polyacrylonitrile (PAN) structure. As a result, a distinctive diffraction peak for the structure was observed at a 2θ value of 17.1 [42]. This peak is clear and strong and has a standard position at the phase (100).…”
Section: Resultsmentioning
confidence: 92%
“…However, the inappropriate disposal of these effluents has caused concern for the scientific community, which challenges applying repairing processes for these environmental damages [4]. Conventional wastewater treatment processes include biochemical methods, centrifugation, ultracentrifugation, thermal treatments, and each of these processes has severe limitations, whether energetic, treatments (thermal and mechanical), or chemical [5]. Techniques that have been receiving more attention due to their energy efficiency use membranes as an active principle for their operation, because it presents a clean technology, simplicity of operation, and has broad applicability, in addition to being possible to combine with other processes [6].…”
Section: Introductionmentioning
confidence: 99%